THE EFFECTIVENESS OF HEALTH EDUCATION IN IMPROVING KNOWLEDGE OF DIARRHEA PREVENTION AMONG SCHOOL-AGED CHILDREN AT SDN SINGONEGARAN 1 KEDIRI CITY, INDONESIA - Kili Astarani; Fira Deshinta Dewi; Fiola Christanti; Felicia Brittenia Elizabeth S.K; Fenly Viola Abraham; Florida Dian Bani; Fipson Usel Suryadi Finit (Pedagogic Research-Applied Literacy Journal, 2026)
Diarrhea remains a significant health problem among school-aged children and is closely associated with inadequate implementation of Clean and Healthy Living Behavior (CHLB). Health education is one of the promotive strategies needed to improve children's knowledge of diarrhea prevention from an early age. This community service program aimed to analyze the effectiveness of health education in improving knowledge of diarrhea prevention among school-aged children at SDN Singonegaran 1 Kediri. The program involved 17 students and was conducted through interactive health education sessions using lectures, PowerPoint presentations, educational videos, leaflets, and demonstrations of proper handwashing with soap (HWWS). Knowledge was evaluated using pre-test and post-test questionnaires, and the data were analyzed descriptively. The findings demonstrated an improvement in students' knowledge following the intervention. The proportion of students with good knowledge increased from 0% to 52.96%, while those with moderate knowledge decreased from 70.58% to 23.52%, and those with poor knowledge decreased from 29.42% to 23.52%. Health education was effective in improving students' knowledge of diarrhea prevention and can serve as a promotive strategy to support the adoption of Clean and Healthy Living Behavior (CHLB) in the school setting.